Genericity - Mari, Alda; Beyssade, Claire; Del Prete, Fabio (Researcher in linguistics) (Oxford studies in theoretical linguistics ;, 2013)
Providing an up-to-date introduction to the study of generics this volume gathers new work from senior and young researchers. It is organised along three main areas of study: the generic and individuals; genericity and time; and the sources of genericity and types of judgment.